The Transformation of the Traditional Balinese House for Tourist Facilities: Managing a Home-Based Enterprise and Maintaining an Architectural Identity - Diasana Putra, I Dewa Gede Agung; Lozanovska, Mirjana; Fuller, Robert (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
As a tourist destination, Bali relies on its culture, which includes socio-cultural activities and the architectural form of the traditional Balinese house inspired by the Hindu Balinese religion, as the main core to attract tourists. The increasing number of tourist arrivals has motivated people to transform their traditional houses become tourist facilities to improve their economic condition. The traditional house-compound becomes a home-based enterprise with the construction of new buildings in their house. This construction has changed the setting, spaces and forms of the house, which are components of an architectural identity. This phenomenon encourages questions about the new relationship between a home-based enterprise and an architectural identity. Is there a conflict between a home-based enterprise as a strategy to gain an economic benefit and an architectural identity as an expression of Balinese culture? Is there an interdependent relationship between them? By examining the setting, forms and transformation process of the traditional Balinese house, this study discusses the continuity of an architectural identity alongside home-based enterprises in the physical transformation of tourist villages. In tourist villages, the architecture identity and home-based enterprise have an interdependent relationship where the architectural identity is an asset to attract tourists and, by running tourist facilities as home-based enterprises, the Balinese people maintain the architectural identity of their houses.